TINGKAT KORUPSI PADA PEMDA PROVINSI JAWA BARAT DAN BANTEN - Fithri, Nurul; Hapsari, Dini Wahjoe (2021)
Corruption is fraud that can harm state finances. Indonesia Corruption Watch shows that the trend of Indonesia's losses due to corruption during the first semester of 2020 reached a total of IDR 39.2 trillion. The purpose of this study is to review the simultaneous and partial effect of audit opinion, audit rectification and fiscal decentralization on the level of corruption of West Java and Banten Provincial Government in 2016-2019. The study used 120 samples taken by purposive sampling method. The result shows that audit opinion has a negative effect on the level of corruption. The samples with the non-unqualified audit opinion have a higher level of corruption than the samples with the unqualified audit opinion. Audit rectification and fiscal decentralization have no partial effect on the level of corruption.